Presence of the Double Bass in the Record Production of the Peruvian Vals Criollo from 1940 to 1960 - Otárola Yllescas, Ricardo León (2017)
The objective of the present research is to identify the many factors that could have determined the inclusion of the double bass in the instrumental accompaniment of Peruvian Criolla music, namely the Peruvian waltz. By analyzing the discography production process, it is observed how the double bass has acquired a significant presence in the Criollo instrumental format. This research addresses the musical contributions of double bassists that took part in the first recordings and presents by means of music transcriptions which instrumental devices, forms, and rhythmic-melodic patterns were used in the recording of waltzes, tools that were reshaped throughout the discography production. As a result of studying the instrument’s process of adaptation and its establishment into popular music, significant chronological data were obtained which will allow understanding of Peruvian music development at large.